Qualitative analysis of vehicle needs and perceptions towards the adoption of a reconfigurable vehicle. (March 2016) - Carvalho, Irene; Costa, Patrícia L.; Simoes, Ricardo; Silva, Arlindo; Silva, Sílvia A.
Abstract: We explore in which extent the notion of a reconfigurable vehicle, presented as an innovation, is an anticipated need given the current patterns of vehicle occupancy. The main goals of this study are: (i) Identify latent needs towards vehicle purchase choices and use; (ii) Characterize the individual perceptions about car use, in general; (iii) Characterize the individual perceptions about the reconfigurable notion of a vehicle, able to be adapted to daily occupancy requirements. The study is based on data from 4 focus groups. To identify that needs data are analyzed through the QFD VOC. Engineering requirements are translated with HOQ. To explore perceptions data are analyzed using a content analysis methodology with MaxQDA10 software©. Within the context of designing vehicles to comply with European regulations on CO2 emissions, the results reveal latent needs in human dimensions of the product. The notion of a reconfigurable vehicle was identified as a latent need for different target markets. Stated barriers for the adoption of this particular vehicle do not fully overlap with what individuals ponder when they consider buying a current fuel-based. Educational background was found to contribute for the receptivity of the disruptive proposal.